Effect of supervised exercise therapy for intermittent claudication in patients with diabetes mellitus - van Pul, Kim M; Kruidenier, Lotte M; Nicolaï, Saskia P A; de Bie, Rob A; Nieman, Fred H M; Prins, Martin H; Teijink, Joep A W (Annals of vascular surgery, 2012)
Primary treatment for patients with intermittent claudication is exercise therapy. Diabetes mellitus (DM) is a frequently occurring comorbidity in patients with intermittent claudication, and in these patients, exercise tolerance is decreased. However, there is little literature about the increase in walking distance after supervised exercise therapy (SET) in patients with both intermittent claudication and DM. The objective of this study was to determine the effectiveness of SET for intermittent claudication in patients with DM. Consecutive patients with intermittent claudication who started SET were included. Exclusion criteria were Rutherford stage 4 to 6 and the inability to perform the standardized treadmill test. SET was administered according to the guidelines of the Royal Dutch Society for Physiotherapy. At baseline and at 1, 3, and 6 months of follow-up, a standardized treadmill exercise test was performed. The primary outcome measurement was the absolute claudication distance (ACD). We included 775 patients, of whom 230 had DM (29.7%). At 6 months of follow-up, data of 440 patients were available. Both ACD at baseline and at 6 months of follow-up were significantly lower in patients with DM (P < 0.001). However, increase in ACD after 6 months of SET did not differ significantly (P = 0.48) between the DM group and the non-DM group (270 m and 400 m, respectively). In conclusion, SET for patients with intermittent claudication is equally effective in improving walking distance for both patients with and without DM, although ACD remains lower in patients with DM.